Financing Technology Transfer - Jacques Darcy; Helmut Kraemer-Eis; Olivier Debande; Dominique Guellec (European Investment Fund (EIF), 2009)
Global policy discussions increasingly focus on innovation and the knowledge economy as a driver of long-term growth. In parallel new forms of innovation processes are emerging, notably open innovation and innovation networks stressing the importance of connections between various stakeholders. Links between universities and the business sector are of particular importance as many inventions come out of universities but have to be further developed to become economically relevant innovations. New financing instruments and attracting private investors to Technology Transfer (TT) are necessary but difficult as the pattern of risk and information in this `in-between area' is complex: Technology is not basic anymore and it requires large amounts of capital to be scaled up – with uncertain market prospects. This paper addresses new financial instruments for TT, building on European Investment Fund's experience in this field.
Keywords: 330